Sensitivity of Service Life Extension and CO2 Emission due to Repairs by Silane Treatment Applied on Concrete Structures under Time-Dependent Chloride Attack - Aruz Petcherdchoo (Advances in Materials Science and Engineering)
This paper presents sensitivity of service life extension and CO2 emission due to silane (alkyltriethoxysilane) treatment on concrete structures under time-dependent chloride attack. The service life is predicted by the Crank–Nicolson-based finite difference approach for avoiding the complexity in solving Fick’s second law. The complexity occurs due to time-dependent chloride attack and nonconstant diffusion coefficient of concrete with silane treatment. At the application time of silane treatment, the cumulative CO2 emission is assessed. The effectiveness of silane treatment is defined as the ratio of the service life extension to the cumulative CO2 emission assessed within the corrosion-free service life. The service life extension is defined as the difference between corrosion-free service life of concrete structures without and with time-based application of silane treatment. From the study, the diffusion of chlorides in concrete with silane treatment is found to be retarded. In comparison, the strategy without deterioration of silanes during effective duration is more suitable for service life extension but less effective than that with deterioration. In the sensitivity analysis, there are up to eight parameters to be determined. The service life of concrete structures without silane treatment is most sensitive to the water-to-cement ratio and the threshold depth of concrete structures. Considering only five parameters in silane treatment strategies, the service life is most sensitive to the first application time of silane treatment. The cumulative CO2 emission is most sensitive to either the first application time of silane treatment or the amount of CO2 emission per application.